Relationship of Work Motivation with the Work Commitment of Cooperative Employees Kencono Wungu Mojokerto - Rr. Hesti Setyodyah Lestari; R. M Mahrus Alie (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the relationship between work motivation and work commitment in the Kencono Wungu Cooperative. The research hypothesis is that there is a positive relationship between work motivation and work commitment of employees at the Kencono Wungu Cooperative. Employees who have high motivation will have a high work commitment as well. Vice versa, employees who have low motivation will have low work commitment as well. A quantitative approach with correlational research was used in this study. Purposive Sampling with 20 subjects as a sampling technique. Some of the research instruments used include validity tests with the results of the validity index of work motivation (x) being 0.934 and work commitment (y) being 0.937. To test the reliability of the variable (x) of 0.934 and the variable (y) of 0.937. Both variables are normally distributed because the results of the normality test show the results of 0.065; p=0.05. And the two variables have a linear relationship because the results of the linearity test are 0.542; p=0.05. The correlation test results show that there is a positive and significant relationship between work motivation and work commitment (r = 0.542; p = 0.000 < 0.05). As a result, the goal is to have a high level of work motivation and a high level of work commitment.